Variation in the phenology of Pygoscelis penguins - Black, C (2017)
Variation in phenology is linked to the timing of environmental variables and influences survival at both the individual and colony level. Therefore, understanding a species' annual cycle is vital to its ecology and conservation. By reviewing literature on Pygoscelis penguin phenology in Chapter 1, I identify major gaps, both spatially and temporally, in our knowledge of the timing of events in the three species (Adeélie, Pygoscelis adeliae; chinstrap, and Pygoscelis antarctica; gentoo, Pygoscelis papua): particularly, 1) during the guard phase, 2) their behaviour in winter, 3) the phenology of colonies inhabiting locations away from scientific bases, and 4) the general phenology of chinstrap penguins. Chapter 2 assesses which time-lapse camera methods are most relevant to seabird research, highlighting the capabilities and limitations of cameras in past studies and how they may be best applied to future research. Chapter 3 examines the timing of the guard phase in gentoo penguins and how chick aggregation behaviours vary across several sites. Chapters 4 and 5 show variation in winter abundance at breeding sites in both gentoo and Adélie penguins related to abiotic factors and colony location. Lastly, Chapter 6 fills in gaps in the known timing and duration of phenology events in gentoo and chinstrap penguins across their full latitudinal ranges, while relating these timings to chick survival. In the conclusion, I summarize the main findings of the thesis, focusing on three major themes that were observed across the four data chapters and their implications: 1) behaviours are not consistent across colony locations 2) nor between years, and these behaviours depend on 3) local environmental conditions. I then synthesize these empirical findings from each of these chapters, discuss the implication of these findings to ecological theory and conservation policy, highlight some of the limitations of these studies, and recommend possibilities for future research.